2003
DOI: 10.1109/tbme.2003.818466
|View full text |Cite
|
Sign up to set email alerts
|

Finite-element modeling of needle electrodes in tissue from the perspective of frequent model computation

Abstract: Information about electric field distribution in tissue is very important for effective electropermeabilization. In heterogeneous tissues with complex geometry, finite-element (FE) models provide one of alternative sources of such information. In the present study, modeling of needle electrode geometry in the FE model was investigated in order to determine the most appropriate geometry by considering the need for frequent FE model computation present in electroporation models. The 8-faceted needle electrode ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
21
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(23 citation statements)
references
References 33 publications
2
21
0
Order By: Relevance
“…Four needle electrode pairs caused the Table IV. least healthy tissue damage; however, they required more current and more healthy tissue to be reversibly electropermeabilized ( Fig. 7(b), Table IV), confirming previous results of our group-more electrodes mean a more invasive procedure, higher needed current, and lower needed voltage to obtain the same target tissue coverage [11], [26]. The 2 × 2 hexagonal needle electrode array caused the least volume of healthy tissue to be reversibly electropermeabilized and more to be irreversibly electropermeabilized (Fig.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Four needle electrode pairs caused the Table IV. least healthy tissue damage; however, they required more current and more healthy tissue to be reversibly electropermeabilized ( Fig. 7(b), Table IV), confirming previous results of our group-more electrodes mean a more invasive procedure, higher needed current, and lower needed voltage to obtain the same target tissue coverage [11], [26]. The 2 × 2 hexagonal needle electrode array caused the least volume of healthy tissue to be reversibly electropermeabilized and more to be irreversibly electropermeabilized (Fig.…”
Section: Discussionsupporting
confidence: 87%
“…However, only after the experimental validation of a numerical model was performed by comparing the numerical calculations to histological examinations of electropermeabilized tissue did numerical modeling gain ground in ECT research [11]. Different geometries of needle electrodes have been since then compared by [14], [26], and [27]; however, none of these included optimization and only Sel et al [28] used a 3-D model. In our study, three needle electrode pairs, four needle electrode pairs, and 2 × 2 hexagonal needle electrode array all gave similar results, whereas the 3 × 3 hexagonal needle electrode array was significantly worse than the others.…”
Section: Discussionmentioning
confidence: 99%
“…It has been clearly demonstrated that the effectiveness of LEDC is highly associated with the distribution of the electric field in the tissue (with the contributing variables including voltage, distance between the electrodes and depth of electrodes insertion) required to reach the optimal electrode configuration and tumor coverage [3,10,36,38,39,40,41]. Irreversible electroporation aims to completely extirpate the tumor or, at least, to dramatically modify the neoplastic microenvironment without damaging the surrounding tissues or vessels.…”
Section: Discussionmentioning
confidence: 99%
“…14,15,19,[24][25][26] We examined the adequacy for ECT of needle electrode array geometries by calculating the values of total electric current through the model (must be as low as possible to avoid nerve stimulation 27 and not exceed the capacities of the electric pulse generator 28 ) and volumes of reversibly and irreversibly electroporated tumor tissue and healthy tissue. Three-needle electrode pairs were best for the spherical and the realistic tumor geometry; they required the lowest total electric current and caused only a small volume of healthy tissue to be irreversibly electroporated (healthy tissue damage) (Figure 4).…”
Section: Discussionmentioning
confidence: 99%